KINERJA PROGRAM KELOMPOK USAHA MANDIRI (KUM) YAYASAN DANA SOSIAL AL-FALAH TERHADAP PERLINDUNGAN MAQASHID SYARIAH - Lazuardi Azhari Laksono; R. M. Qudsi Fauzi, M.M. (Universitas Airlangga, 2018)
This study is done to know the performance of Yayasan Dana Sosial Al-FalahIndependent Business Groups (KUM) program toward maqashid syariah protection. The background of the study is accountability responsibility of LAZ over funding management of ZIS which entrusted to benefactor of LAZ especially YDSF. In this case, the quality of performance which talked about is the protection toward maqashid syariah which receives funding from Independent Business Groups program. This study is a qualitative research. The approach of this research uses case-study strategy. The data collection used in this study is interview method; after collecting data, it is continued with reducting data, presenting data, and drawing conclusion. The research shows that YDSF Independent Business Groups program with various activities within has a performance with good criteria. Its good performance is measured with protected several aspects from mustahiq of YDSF Independent Business Groups, those aspects are; religion, intellectual, and wealth. REFERENCESAl-Qur’an. Departemen Agama Republik Indonesia, Edisi Baru Cetakan 2005.Jakarta: Pustaka Amani Jakarta.Ali Hasan, M. 2008. Zakat dan Infak Salah satu solusi mengatasi problema sosial di indonesia. Jakarta: Kencana prenda media grup.Bungin, M Burhan. 2007. Penelitian kualitatif: komunikasi ekonomi, Kebijakan publik, dan ilmu sosial lainnya. Jakarta: Kencana Prenada Media Grup.Djamil, Faturrahman. 1995. Metode Majelis Tarji Muhammadiyah. Jakarta: Logos.Hafidhuddin, Didin. 2002. Zakat Dalam Perekonomian Modern. Jakarta: Gema Insani Press.Hasibuan, M. 2001. Manajemen Sumber Daya Manusia. Jakarta: Bumi Aksara.Jaelani, A. (2008). Pengaruh kualitas pelayanan dan social marketing lembaga amil (LAZ) terhadap keputusan ber zakat muzakki (studi kasus: pada rumah zakat Indonesia). Master’s thesis, Jakarta: Universitas Indonesia.Mafrudloh, Shoimataul. 2009. Analisis Faktor-Faktor yang Mempengaruhi Pengumpulan Dana ZIS pada Lembaga Pengelolaan Dana Zakat di Provinsi Jatim. Skripsi tidak diterbitkan. Surabaya: Universitas Airlangga Surabaya.Mangkunegara, Anwar Prabu. 2010. Evaluasi Kinerja Karyawan SDM. Refika Jakarta: Aditama.Miles and Huberman. 1992. Qualitative Data Analysis. California: Sage Publication Inc.Moleong. 2002. Metode Penelitian Kualitatif. Bandung: PT Rosda Karya.Nazir, Muhammad. 2005. Metode penelitian. Bogor: Ghalia Indonesia.Onny S, Prijono dan Pranarka A M W. 1996. Pemberdayaan : Konsep, Kebijakan dan Implementasi. Jakarta: CSIS.P3EI. 2008. Ekonomi islam. Jakarta: Rajawali Press.Qardhawi, Yusuf. 1999. Hukum Zakat. Jakarta: PT Pustaka Litera Antar Nusa.Ryandono, Muhammad Nafik Hadi. 2010. Ringkasan disertasi: peran dan pengaruh penghimpunan dana terhadap penyaluran dana dan faktor kinerja bank serta kesejahteraan karyawan bank islam di indonesia.Stonner, James A F. 1996. Manajemen. Edisi II. Jakarta: Prenhalindo. Sugiyono. 2009. Memahami Penelitian Kualitatif. Bandung: AlfabetaSulistiyani, Ambar Teguh. 2003. Manajemen Sumber Daya Manusia. Yogyakarta: Graha Ilmu.Sumodiningrat, Gunawan. 2002. Memberdayakan Masyarakat Perencana. Jakarta: Kencana Nusadwina.Suprayitno, Eko. 2005. Ekonomi Islam: Pendekatan Ekonomi Makro Islam danKonvensional. Yogyakarta: Graha Ilmu.Suyanto, M. 2008. Muhammad Business and Strategy Ethics. Yogyakarta. Andi Offset.Tasmara, Toto. 2008. Membudayakan Etos Kerja Islami. Jakarta: Gema Insani.Yin, Robert K. 2012. Studi Kasus Desain dan Metode. Jakarta: PT Raja Grafindo Persada.